FINANCIAL FEASIBILITY ANALYSIS OF DODOL BUSINESS IN TANJUNG PURA DISTRICT, LANGKAT REGENCY - Hamizan Hikmah; Thursina Mahyuddin; Muhammad Jamil (RADJA PUBLIKA, 2025)
This study aims to determine the feasibility of the dodol business in Tanjung Pura District, Langkat Regency. The sampling technique in this study used probability sampling, using equal opportunities for members of the population to become sample members. The data collected in this study were primary data and secondary data. The data analysis method used in this study was the financial analysis method, calculating income, and R/C Ratio. The subjects of this study as informants were entrepreneurs/owners of dodol in Paya Perupuk Village and Pematang Tengah Village, Tanjung Pura District. Based on the results of the financial feasibility analysis, the results of this study were that the dodol business in Tanjung Pura District earned income of Rp5,268,000,000/Year, production costs of Rp1,952,399,300/Year, annual income of Rp3,315,600,700/Year. The R/C Ratio value obtained is 2.70 so that it can be seen that the R/C value is >1, the BEP of Revenue is Rp17,086,705.74 and the Revenue generated exceeds the BEP of revenue which is Rp181,655,051.73, the BEP of production is 320.05 Kg and the production generated exceeds the BEP of production generated, which is 3,252.41 Kg. it can be concluded that the dodol business in Tanjung Pura District, Langkat Regency is feasible to be run further.